'Yarning up with Koori kids' – hearing the voices of Australian urban Indigenous children about their health and well-being. Issue 6 (2nd November 2017) - Priest, Naomi; Thompson, Laura; Mackean, Tamara; Baker, Alison; Waters, Elizabeth
ABSTRACT: Objective: Australian Indigenous children experience some of the most substantial health inequalities globally. In this context, research regarding their health and well-being has overemphasised physical illnesses with limited exploration of a diverse range of dimensions and determinants, particularly those based on Indigenous holistic understandings of health and well-being. This deficit-based approach has thus missed many strengths and assets of Indigenous children. This research aimed to gain insight into the perspectives of Indigenous children about their health and well-being in an urban setting in Australia. It joins a limited international literature examining views and experiences of non-majority children. Design: Participatory and qualitative child-friendly research methods were utilised. The project was developed in partnership with Indigenous community organisations and members. Photo-elicitation activities and focus groups were conducted with 31 Indigenous children aged 8–12 years. Qualitative data were analysed thematically, combining focus group and interview data. Results: It was evident an urban Indigenous child perspective of health and well-being includes rich understandings of the interconnectedness of physical, social-emotional and cultural dimensions of holism, as well as the integral importance of family and community relationships. The study also found that specific worries regarding loss of loved ones and racism were highly salient in Indigenous children's lives. Conclusion: The overwhelming conclusion to be drawn from this research is that Indigenous children in urban areas need ongoing recognition of both their agency and resilience in the face of adversity, within a wider context of historical and contemporary racialisation and racism.